Concurrent droughts and hot extremes in northwest China from 1961 to 2017. (13th December 2018) - Li, Xin; You, Qinglong; Ren, Guoyu; Wang, Suyan; Zhang, Yuqing; Yang, Jianling; Zheng, Guangfen
Abstract : Northwest China forms the main part of the arid and semiarid areas in China, and even includes some extremely arid areas. This zone of interaction is affected by the westerlies and monsoons making it sensitive to global climate change. Drought is the main type of natural disaster affecting northwest China. Global warming has caused a gradual strengthening of the frequency and intensity of hot extremes, when dry conditions and heatwaves occur simultaneously or successively; as a result, that socioeconomic risks can increase considerably. The present study examined changes in concurrent droughts and hot extremes in northwest China during 1961–2017 based on data from 119 meteorological stations. The result shows that the frequency of concurrent droughts and hot extremes exhibited an increasing trend over most parts of northwest China, while a negative trend occurred in western Xinjiang and at some sites in Qinghai. Concurrent droughts and hot extremes appeared more often in May in western Xinjiang, and in summer in other parts of northwest China. Overall, the trends of such concurrent events, regardless of different definitions, increased from 1961–2017 over northwest China. In particular, from 1981–2017, the trend rose more significantly than in other decades, and reached an abrupt point of change in 1996. Although the trend changed from a positive significant signal to a negative one from 2001–2017, the trend grew 2–3 times from 1997–2017. Changes in large‐scale atmospheric circulation show that an anticyclonic circulation strengthened, increasing in geopotential height over the midhigh latitudes of Eurasia and was centred on Mongolia and Lake Baikal. This enhanced relative humidity in western Xinjiang and eastern Qinghai, and weakened it elsewhere from 1997–2017. These changes have contributed to the changes in the spatial distribution and trends in concurrent droughts and hot extremes in northwest China. Abstract : Variations in the number of concurrent droughts and hot extremes for the period of 1961–2017 in northwest China. Red line for DH85, blue line for DH90 . DH85 and DH90 indicate simultaneous a month 3‐month SPEI < −1.0 and hot extremes during which the daily maximum temperature exceeded the 85th and 90th percentiles for at least three consecutive days, respectively.